The Effects of Europeanization on the Integration Process in the Upper Adriatic Region - Nadalutti, Elisabetta (Springer, 2015)
This book examines the effects of Europeanization on two cross-border states, Italy and Slovenia, in the period between 1990 and 2012. It does so by means of an analysis of specific funding programmes such as Interreg and Phare. The book explores whether Europeanization, through cross-border cooperation, has promoted a post-national mode of governance and new relations between the national, the supra-national and the local-regional level. It discusses whether a link can be established between the activities of sub-national actors (municipalities, regions) and the recent development of legal instruments designed to enhance cross-border cooperation. Taking the perspective of citizenship and focusing on ethnic minority groups and cultural-social associations, the book addresses the question of whether a new notion of citizenship, multi-layered and multi-dimensional, has emerged in cross-border areas through cross-border cooperation. ​